Psychological Wellbeing and Personality Mental Health - Zotova, O; Karapetyan, L (KnE Life Sciences, 2018)
Wellbeing is a multifaceted phenomenon with regard to its conceptualization, fields of application, discourse practices and a great number of components. Its greatest advantage resides in health improvement and lifespan increment. Health can be considered as a source of physical and mental force, as an adaptive ability of the organism, an ideal and meaning of life, an ideal state of the individual who feels well. The aim of the study was to examine socio-psychological features of the respondents with different degrees of subjective wellbeing and health self-esteem pronouncement. As a result, the four groups involving 202 testees were singled out. The survey showed that both health self-esteem and subjective wellbeing serve as predictors not only of attitude towards the world and the self but also as a certain “frame” through the prism of which the person perceives the world around. It was revealed that the respondents with low health self-esteem are emotionally unstable, prone to neuroticism and dissatisfaction with their life in general. The group of the testees with high health self-esteem and high level of subjective wellbeing are characterized by proactive attitude, a zest for life, positive self-esteem, lack of sustainable tension, while the respondents with low level of subjective wellbeing and low health self-esteem exhibit an increased level of neuroticism, significance of their social environment and preoccupation with their own emotional sensations. The search for individual and typological specific features depending on the person’s subjective perceptions about his health and wellbeing allows for revealing idiosyncratic “syndromes” of individual consciousness. Keywords: subjective wellbeing, mental health, typology.